Pemodelan Integrasi Pengaruh Penerapan ISO 9001:2008 terhadap Kinerja dan Produktivitas Karyawan - Arif Rahman (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2017)
Entering the commercial printing business, PT. XYZ competes withmany competitors. One of the best waysto take part in the competion is byincreasing productivity and implementing a quality management system ISO 9001: 2008. The research objective is to produce a model that can integrate the effect of the ISO 9001: 2008application into employee performance and productivityimprovement. Data aregenerated from the sample consisting of 100 respondents selected byemployee’s position level, namely coordinator and above. The samples are selected using purposive sampling method. This study employsa path analysis by applying Linear Structural Relationships (Lisrel 8.80) and SPSS 16 softwares. This study usesa path analysis of 5 latent variables, namely planning for the certification of ISO 9001: 2008, company’s commitment, procedure implementation, employee’s performance and productivityimprovement. The result shows two mathematical equations, with the first onestating the application of ISO 9001: 2008 has a simultaneously positive effect on employee’s performance,while the second one stating the application of ISO 9001: 2008 and employee’s performance produce simultaneously positive effects on productivity improvement. Verification and validation tests showthe model has a very good fit, as seen bytheChi-Square value of 0.00. Besides, it also has a probability value of P = 0 <0.05,indicating that the collected empirical data are identical with the theory formulated based on the path analysis.